Understanding acute ankle ligamentous sprain injury in sports - Fong, D. T. P.; Chan, Y.-Y.; Mok, K.-M.; Yung, P. S. H.; Chan, K.-M. (Sports Medicine, Arthroscopy, Rehabilitation, Therapy & Technology (SMARTT), 2009)
This paper summarizes the current understanding on acute ankle sprain injury, which is the most common acute sport trauma, accounting for about 14% of all sport-related injuries. Among, 80% are ligamentous sprains caused by explosive inversion or supination. The injury motion often happens at the subtalar joint and tears the anterior talofibular ligament (ATFL) which possesses the lowest ultimate load among the lateral ligaments at the ankle. For extrinsic risk factors to ankle sprain injury, prescribing orthosis decreases the risk while increased exercise intensity in soccer raises the risk. For intrinsic factors, a foot size with increased width, an increased ankle eversion to inversion strength, plantarflexion strength and ratio between dorsiflexion and plantarflexion strength, and limb dominance could increase the ankle sprain injury risk. Players with a previous sprain history, players wearing shoes with air cells, players who do not stretch before exercising, players with inferior single leg balance, and overweight players are 4.9, 4.3, 2.6, 2.4 and 3.9 times more likely to sustain an ankle sprain injury. The aetiology of most ankle sprain injuries is incorrect foot positioning at landing - a medially-deviated vertical ground reaction force causes an explosive supination or inversion moment at the subtalar joint in a short time (about 50 ms). Another aetiology is the delayed reaction time of the peroneal muscles at the lateral aspect of the ankle (60-90 ms). The failure supination or inversion torque is about 41-45 Nm to cause ligamentous rupture in simulated spraining tests on cadaver. A previous case report revealed that the ankle joint reached 48 degrees inversion and 10 degrees internal rotation during an accidental grade I ankle ligamentous sprain injury during a dynamic cutting trial in laboratory. Diagnosis techniques and grading systems vary, but the management of ankle ligamentous sprain injury is mainly conservative. Immobilization should not be used as it results in joint stiffness, muscle atrophy and loss of proprioception. Traditional Chinese medicine such as herbs, massage and acupuncture were well applied in China in managing sports injuries, and was reported to be effective in relieving pain, reducing swelling and edema, and restoring normal ankle function. Finally, the best practice of sports medicine would be to prevent the injury. Different previous approaches, including designing prophylactice devices, introducing functional interventions, as well as change of games rules were highlighted. This paper allows the readers to catch up with the previous researches on ankle sprain injury, and facilitate the future research idea on sport-related ankle sprain injury.